Robust Correlation based True-Speed-over-Ground Measurement System employing a FMCW Radar - Reißland, Torsten; Lenhart, Björn; Lichtblau, Johann; Sporer, Michael; Weigel, Robert; Kölpin, Alexander (2018 15th European Radar Conference (EuRAD), 2018)
This paper presents a novel approach for the determination of True-Speed-Over-Ground for trains. Speed determination is accomplished by correlating the received signals of two side-looking radar sensors. The theoretically achievable precision is derived. Test measurements are done to give a prove of concept. The measurements are done in two different scenarios. The test measurements are carried out using a bi-static 24 GHz frequency modulated continuous wave (FMCW) rada
Keywords: radar; fmcw; correlation; sar; velocity; train